DURIO MACRANTHA KOSTERM., SPECIES NOYA (BOMBACACEAE) FROM NORTH SUMATRA - a. j. g. h. kostermans (BRIN Publishing (Penerbit BRIN), 1992)
An interesting species of Durio from Sumatra is described and illustrated from a living specimen growing in Bogor.